PENURUNAN PAJAK EKSPOR DAN DAMPAKNYA TERHADAP EKSPOR MINYAK KELAPA SAWIT INDONESIA KE CINA (PENDEKATAN ERROR CORRECTION MODEL) - Ernawati Munadi (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2007)
The palm oil Industry is an important sector in the Indonesian economiy as it is one of the country’s major export earners as well as food source for her population.Indonesia is the world second largest producer of palm oil after Malaysia, accounting for about 34% OF The world production in the year 2006. Indonesia is also the largest consumer of palm oil in the developing economies, in 2006. Indonesia consumed a total of 5.5 mn tonnes of palm oil. Of this amount 76.75% is comprised of frying oil. About 55% of the production is exported in the form of crude palm oil mainly to Asian countries primarily to India and China and Eruropean countries. Debate on Indonesia’s palm oil policy was stimulated by the sharp increase in cooking oil prices in 1994-1995 which resulted in the introduction of export tax rate on palm oil in order to maintain a certain level of domestic consumption.Using annual data for the period 1969-2006, an econometric approach mainly the error correction model. Was employed in this study This paper examines the impacts of reduction in export duty onthe import demand of Indonesian palm oil to China. The findings indicate that the quantity of palm oil exported to China is significantly influenced by changes in the soybean oil price, world palm oil price, Industrial Production Index (IPI) exchange rate and lagged of export demand of Indonesian palm oil to China by one year with the elasticity of 1,49, 1.47,0.24, 0.59, and 0.79, respectively. The coefficients for long run variables presented by the ECM are jointly not equal to zero.This result suggests that as a group, the long run variable (ECM) have influenced the changes in the export demand to China which is indicated by the significance of the coefficient. The simulation results suggest that the direct impact of reduction of export duty would increase the quantity exported to China. The Indonesia export to China from 95.36 thousand tones to 118,23 thousand tones.